THE CHEMISTRY OF SOME EXTRACTIVES FROM PLANTS OF THE FAMILY RUTACEAE (1970)
Chemically, the Rutaceae family is probably the most versatile of all higher family of plants. Three main groups of compounds, namely, limonoids, coumarins and quinoline alkaloids have been obtained from this family. The LLtroductory part of this work reviews very briefly the chemistry of each of these groups. In the main work, three plants of the West African genera of the Rutaceae were investigated. The wood of Afraegle peniculata (Schum and Thonn) yielded the furocoumarin, imperatorin which was isolated earlier from a number of Rutaceous plants and in addition, a furoquinoline alkaloid, dictamnine which had also been isolated from a large number of other genera of the family. The root of Clausena aniaata was shown to contain imperatorin along with a new coumarin (coumarrayin) which was shown almost at the same time by Dreyer to be a constituent of Murraya paniculata. From the wood of Oricia suaveolens was isolated a new alkaloid related to Flindersine (an alkaloid from an Australian Rutaceae plant) The structure of the new alkaloid was elucidated from spectroscopic studies to be 1-methyl-6, 7-dimethoxy-flinderslnc and this structure was confirmed synthetically.